TINGKAT PEMANFAATAN WEBSITE DIREKTORAT JENDERAL PAJAK OLEH AKUNTAN DI WILAYAH KALIMANTAN TIMUR - Muhammad Subhan Abd. Gafur (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2015)
This research aimed to examine the effect of acceptance of usability, acceptance ease of use and psychological influences to attitude in using information technology. Attitude will influence the behavior specifically in utilizing information technology concern shown by the behavior. Data was obtained through the questionnaire survey with a purposely sampling technique with the criteria,accountants who utilize tax website that www.pajak.go.idin performing their work. Accountants who are being sampled of this study is accountants in private companies. Analysis of the data in this research uses Structura lEquation Modeling (SEM) with an alternative method of PLS(Partial Least Square) which is assisted with the application program Smart PLS.Based on the results of the research be concluded that 1) there is no significant relationship between perceived usefulness and attitude variables in the utilization of tax website (www.pajak.go.id.); 2) there is a significant relationship between the variables of perceived ease of use and attitude in the use of website taxation (www.pajak.go.id); 3) there is no significant relationship between the variables of psychological attachment and attitude in the utilization of tax website (www.pajak.go.id); 4) there is a significant relationship between attitude and behavior variables intention to use the website taxation(www.pajak.go.id).